Effect of acute Cu exposure on immune response mechanisms of golden cuttlefish (Sepia esculenta). Issue 130 (November 2022) - Bao, Xiaokai; Li, Yan; Liu, Xiumei; Feng, Yanwei; Xu, Xiaohui; Sun, Guohua; Wang, Weijun; Li, Bin; Li, Zan; Yang, Jianmin
Abstract: Sepia esculenta is a common economic cephalopod that has received extensive attention due to the tender meat, rich protein content and certain medicinal value thereof. Over the past decade, multiple industries have discharged waste into the ocean in large quantities, thereby significantly increasing the concentration of heavy metals in the ocean. Copper (Cu) is a common heavy metal in the ocean. The increase of Cu content will affect numerous biological processes such as immunity and metabolism of marine organisms. High concentrations of Cu may inhibit S. esculenta growth, development, swimming, and other processes, which would significantly affect its culture. In this research, transcriptome analysis is used to initially explore Cu-exposed S. esculenta larval immune response mechanisms. And compared to control group with normally growing larvae, 2056 differentially expressed genes (DEGs) are identified in experimental group with Cu-exposed larvae. The results of DEGs functional enrichment analyses including GO and KEGG indicate that Cu exposure might promote inflammatory and innate immune responses in cuttlefish larvae. Then, 10 key genes that might regulate larval immunity are identified using a comprehensive analysis that combines protein-protein interaction (PPI) network and KEGG functional enrichment analyses, of which three genes with the highest number of protein interactions or involve in more KEGG signaling pathways are identified as hub genes that might significantly affect larval immune response processes. Comprehensive analysis of PPI network and KEGG signaling pathway are used for the first time to explore Cu-exposed S. esculenta larval immune response mechanisms. Our results preliminarily reveal immune response mechanisms of cephalopods exposed to heavy metals and provide valuable resources for further understanding mollusk immunity. Highlights: This study is the first to represent the transcriptome analysis based on protein interaction network in cephalopods. It provides valuable gene resources for further study of the immune responses mechanisms in invertebrate larvae. The data serve as a foundation for further research on the cooper-exposed of invertebrates.